PEMBELAJARAN MENULIS CERITA FANTASI MENGGUNAKAN MODEL PROJECT BASED LEARNING - Irmawati, Ai; Khoirunnisya, Khoirunnisya; Aeni, Eli Syarifah (IKIP Siliwangi, 2019)
Writing a fantasy story is a learning activity that is considered less understood by learners, it is seen in the results of students who do not achieve indicators of success of learning, it happens because the process given the teacher does not use learning models in accordance with the material taught so that learners less understand the material described by the teacher. Based on the above, the study of fantasy story text writing is done by using the learning model of Project Based Learning on SMP side. The method used in this research is quasi-experimental design. This study aims to improve the ability of learners in writing fantasy stories according to the curriculum 2013 revised edition and students are expected to be more creative in writing. The object of this study is the work of junior high school students amounted to 30 people on learning to write a fantasy story using the model of Project Based Learning. The result of the treatment at the school was very effective, it is seen from the result of the student test during the pre-test 70,63 and post-test 81,17 so it shows the significant difference with the difference of value 10,54.